PEMBUATAN ANTENA MIKROSTRIP PHASED ARRAY DENGAN PENGATURAN FASA MENGGUNAKAN VARIASI PANJANG SALURAN CATU - Firdaus firdaus (Elektron : Jurnal Ilmiah, 2013)
A microstrip phased array width phase is controlled by length of line feeder is presented in this paper for application in RADAR system. The microstrip array antenna is built from dipolelike individual elemen at center frequency 650 MHz. Five different length transmission lines are used to change current phase feeding in to the antenna which is 2λ, 2.125 λ, 2.025 λ, and 2.5 λ. The measured result reveal exelent agreement width the simaltions. The different length of transmission line able to change the radiation pattern which are 60o, 150o,210o dan 0o.